SPE Improved Oil Recovery Symposium 2010
DOI: 10.2118/129976-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive EOR Study Using Low Salinity Water in Sandstone Reservoirs

Abstract: It has been reported that the ionic strength of injection water can have a major impact on the recovery of hydrocarbons during waterfloods, with increased recovery resulting from the use of low salinity brines. Understanding how the water and oil chemistry affects the final recovery from a physicochemical point of view is necessary in order to optimize low salinity water flooding process. It is clear from the literature over the last two decades that wettability is considered a key factor in achieving the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Therefore, chemical reactions with carbonate particles are also expected to be dramatically different. In sandstone reservoirs, clays control the interaction, especially with the low salinity level of water (Zhang and Morrow 2006;Alotaibi et al 2010). But, in carbonate reservoirs, the effect of salinity is more pronounced.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chemical reactions with carbonate particles are also expected to be dramatically different. In sandstone reservoirs, clays control the interaction, especially with the low salinity level of water (Zhang and Morrow 2006;Alotaibi et al 2010). But, in carbonate reservoirs, the effect of salinity is more pronounced.…”
Section: Resultsmentioning
confidence: 99%
“…These have demonstrated its successful application in other laboratory experiments and field trials (e.g. Loaharjo et al, 2007;Lager et al, 2008a;2008b;Patil et al, 2008;Alotaibi et al, 2010;Cissokho et al, 2010; see, for example, Figure 1a Seccombe et al, 2010). Moreover, there has been increasing focus on the collection of laboratory data to explain the LSE, including contact angles (e.g.…”
Section: Introductionmentioning
confidence: 86%
“…Thermal energy in combination with LSW water flooding, in the form of hot LSW water flooding, can be applied to simultaneously decrease the viscosity of the heavy oil and alter the wettability of the porous media to attain higher oil recovery. Alotaibi et al and Tang et al reported lower contact angle and higher oil recovery, respectively, after increasing the displacement temperature in LSW injection [62,63]. Contrary to this observation, Soraya et al [64] found lower oil recovery at higher temperatures by tertiary LSW.…”
Section: Lsw/hot Water Hybrid Eor Techniquementioning
confidence: 94%